2020
DOI: 10.1002/cctc.201901944
|View full text |Cite
|
Sign up to set email alerts
|

A New Porous Ni‐W Mixed Metal Phosphonate Open Framework Material for Efficient Photoelectrochemical OER

Abstract: Photoelectrochemical water oxidation or oxygen evolution reaction (PEC‐OER) at the semiconductor surfaces has attracted huge attention over the years as it plays key role for energetically demanding processes like fuel cells, water splitting, and rechargeable metal‐air batteries. Thus, development of sustainable, abundant and economical semiconductor nanomaterials as the catalyst for photoelectrochemical water oxidation reaction is very challenging in achieving high efficiency in the overall water splitting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Bhaumik and co-workers reported a new porous Ni-W mixed metal phosphonate hybrids (NiWPPA-4) with open framework structure through simple hydrothermal synthesis. [124] The synthesized NiWPPA-4 hybrids behave as excellent catalyst with ultrahigh activities for photoelectrochemical water oxidation in alkaline pH. It was revealed that synergistic Ni-W bimetallic sites incorporated into hybrid framework with nanoscale porosity as well as remarkable semiconducting property are responsible for outstanding photoelectrochemical activity.…”
Section: Metal Complexes As Catalytic Sitesmentioning
confidence: 98%
See 2 more Smart Citations
“…Bhaumik and co-workers reported a new porous Ni-W mixed metal phosphonate hybrids (NiWPPA-4) with open framework structure through simple hydrothermal synthesis. [124] The synthesized NiWPPA-4 hybrids behave as excellent catalyst with ultrahigh activities for photoelectrochemical water oxidation in alkaline pH. It was revealed that synergistic Ni-W bimetallic sites incorporated into hybrid framework with nanoscale porosity as well as remarkable semiconducting property are responsible for outstanding photoelectrochemical activity.…”
Section: Metal Complexes As Catalytic Sitesmentioning
confidence: 98%
“…Heterogeneous catalysis plays a vital role in chemical transformations (e.g., energy related fields, asymmetric catalysis, and pharmaceutical synthesis), [119][120][121] where the development of low-cost and high-efficient catalysts has been considered to be the key to breaking performance bottlenecks. [122][123][124] The design of homogeneous catalysts not only needs to consider how to improve the activity and selectivity, but also needs to solve the difficulty of catalyst/product separation due to the same phase of catalysts with the reactants in a heterogeneous reaction. Thus, the design of highly stable, active, selective, and easily recyclable catalysts is very essential for sustainable chemical production.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…While currently, transition‐metal phosphate and phosphonate are acting as typical representatives of the burgeoning non‐noble metal electrocatalysts because they are low‐cost, environmentally benign, and present high stability, unique physicochemical characteristics and tunable multifunctionality. The presence of strong affinity between transition‐metal centers and phosphate/phosphonate ligands leads to the design of a large variety of transition‐metal phosphate and phosphonate materials [7–9] …”
Section: Introductionmentioning
confidence: 99%
“…The presence of strong affinity between transition-metal centers and phosphate/phosphonate ligands leads to the design of a large variety of transition-metal phosphate and phosphonate materials. [7][8][9] Transition-metal phosphate is a purely inorganic material composed of the binding of metal centers with phosphoric acid, which are prone to form a layered structure with an open framework. It possesses a good protonic conductivity and variable oxidation states of the metal species, which would enrich the redox behavior and thus is favorable when used as electrodes.…”
Section: Introductionmentioning
confidence: 99%